A Distinction Without a Difference? Examining the Causal Pathways Behind Ideologically Motivated Mass Public Shootings. Issue 3 (August 2018) - Capellan, Joel Alfredo; Anisin, Alexei
This study utilizes crisp-set qualitative comparative analysis to assess 306 mass shootings. We compare non-extremist and extremist mass shooters according to characteristics that capture mental health histories of offenders, their grievances, and strains. We discover that offenders who sympathized with extremism were driven by grievance against a social group and were suffering from either mental health issues or from general strain. Extremist sympathizers differ from non-extremists in the nature of their grievances and the strains they experience. These results imply there may exist different causal mechanistic activity underpinning extremist and non-extremist violence, specifically with regards to mass shootings.